2014
DOI: 10.1002/wrna.1224
|View full text |Cite
|
Sign up to set email alerts
|

tRNA synthetase: tRNA aminoacylation and beyond

Abstract: The aminoacyl-tRNA synthetases are prominently known for their classic function in the first step of protein synthesis, where they bear the responsibility of setting the genetic code. Each enzyme is exquisitely adapted to covalently link a single standard amino acid to its cognate set of tRNA isoacceptors. These ancient enzymes have evolved idiosyncratically to host alternate activities that go far beyond their aminoacylation role and impact a wide range of other metabolic pathways and cell signaling processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
118
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 249 publications
(323 reference statements)
0
118
0
2
Order By: Relevance
“…Further analysis will be required to determine if the genes for the mitochondrial enzymes respond to other cellular stresses. For the cytoplasmic enzymes, there appears to be no obvious correlation between the AA-responsive ARS genes and: (i) essential versus non-essential AA; (ii) Class 1 or Class 2 ARS protein structure; (iii) members of the multi-synthetase complex; or (iv) ARS proteins that are known to have additional, non-canonical activities (9,10,13). Related to gene specificity, there are additional questions raised by our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further analysis will be required to determine if the genes for the mitochondrial enzymes respond to other cellular stresses. For the cytoplasmic enzymes, there appears to be no obvious correlation between the AA-responsive ARS genes and: (i) essential versus non-essential AA; (ii) Class 1 or Class 2 ARS protein structure; (iii) members of the multi-synthetase complex; or (iv) ARS proteins that are known to have additional, non-canonical activities (9,10,13). Related to gene specificity, there are additional questions raised by our results.…”
Section: Discussionmentioning
confidence: 99%
“…Global gene expression profiling, along with other functional studies, has demonstrated that Atf4-upregulated genes are involved in a broad spectrum of cellular functions and includes many members of AA tRNA synthetase (ARS) gene family (2,47). ARSs are a ubiquitously expressed and evolutionally conserved family of enzymes that link an AA to its cognate tRNA (8,9). This primary function of ARSs is highly conserved for all living organisms from bacteria to humans, but secondary functions of many ARSs are also quite common (913).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aminoacyl-tRNA synthetases (ARSs) are generally considered as "housekeepers" involved in protein synthesis, whose primary function is to catalyze the aminoacylation of transfer RNAs (tRNAs). This enzymatic reaction is conserved and proceeds mainly in two steps 1,2 . First, an amino acid and an adenosine triphosphate (ATP) molecule bind to the active site of the corresponding ARS to form an aminoacyl adenylate (amino acid-AMP) intermediate and simultaneously release a pyrophosphate (PPi).…”
Section: Introductionmentioning
confidence: 99%
“…Specific features of tRNAs, called identity elements, allow aminoacyl-tRNA synthetases to distinguish the different amino acid-acceptor classes when charging tRNAs with their cognate amino acid. [4][5][6][7] In addition to the anticodon, structural information and nucleotide 73, the unpaired 3 0 -terminal position immediately before the CCA end, are often used as identity elements. The latter is therefore also called discriminator position/nucleotide/base.…”
Section: Introductionmentioning
confidence: 99%